1 Large-scale tractography of the anterior limb of the internal capsule: predictors of capsulotomy outcomes in obsessive compulsive disorder. Issue 8 (20th July 2020) - Zhang, Chencheng; Kim, Seung-Goo; Li, Jun; Zhang, Yingying; Lv, Qiming; Zeljic, Kristina; Gong, Hengfen; Zhan, Shikun; Lin, Guozhen; Sun, Bomin; Wang, Zheng; Voon, Valerie
Abstract : Objectives/Aims: Surgical procedures targeting the anterior limb of the internal capsule (aLIC) can be effective in medically refractory obsessive-compulsive disorder (OCD). The aLIC consists of white-matter tracts connecting cortical and subcortical structures. Here we assess how specific aLIC tracts are affected in OCD and which tracts predicts improvement post-capsulotomy. Methods: Large-scale diffusion imaging was used to compare detailed white- matter connectivity via aLIC between OCD patients (n=100) and healthy controls (n=88). For each individual, the fractional anisotropy and tract counts were calculated for each white-matterfiber bundle connecting a functionally defined prefrontal and subcortical region. Correlations between tractography measures and pre- and post- capsulotomy clinical outcomes (in obsessive-compulsive, anxiety and depression scores 6 months after surgery) were assessed in 41 OCD patients. We focused on the dorsolateral prefrontal cortex and dorsal cingulate, regions implicated in prediction of capsulotomy and stimulation outcomes. Results: Hierarchical clustering dendograms show an aLIC organization clustering lateral and dissociating ventral and dorsal prefrontal-thalamic tracts highly relevant to targeting. OCD patients had lower aLIC fractional anisotropy across prefrontal cortical-subcortical regions compared to healthy controls (p=0.023, FDR-adjusted). Greater fractional anisotropy and tract counts of the dorsolateral prefrontal-thalamic and -subthalamic tracts in OCD patients predicted greater post-capsulotomy obsessive-compulsive improvements. In contrast, greater counts of the dorsal cingulate-thalamic tracts predicted surgical outcome mediated by depressive and anxiety improvements. Conclusions: These findings shed light on the critical role of the aLIC in OCD and potentially leads towards precision targeting to optimize outcomes as a function of symptom dimension in OCD.